2010
DOI: 10.1039/b915689e
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics study of the hydration of Li+, Na+ and K+ in a montmorillonite model. Influence of isomorphic substitution

Abstract: The present work reports ab initio molecular dynamics simulations, based on density functional theory using the PBE functional, of Li(+)- Na(+)- and K(+)-montmorillonites, considering three types of isomorphic substitutions in the montmorillonite layer: tetrahedral (T(sub)), octahedral (O(sub)) and both (OT(sub)). These simulations allow us to evaluate the effect of each type of substitution on the inner- outer-sphere complex formation of the alkali cations. It is observed that, for the three kinds of substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
83
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 58 publications
13
83
2
Order By: Relevance
“…It could be observed that there were alternate potential states in MMT layer where the O atoms in MMT were located at the potential valley due to their negative mulliken charge while the Al, Mg, Si atoms were located close to the potential peak due to their positive Mulliken charge. The similar behavior was reported by several studies [51,52]. A closer look at Fig.7 indicated that there were valleys around z= 0.42 and 0.47 in M(001)W-1 and M(010)W-1, respectively, corresponding to the location of both the adsorbed water molecules with negative Mulliken charge of -0.03 e. These valleys above surface were able to provide adsorption active sites for new species, such as water molecules.…”
Section: Charge Analysissupporting
confidence: 86%
“…It could be observed that there were alternate potential states in MMT layer where the O atoms in MMT were located at the potential valley due to their negative mulliken charge while the Al, Mg, Si atoms were located close to the potential peak due to their positive Mulliken charge. The similar behavior was reported by several studies [51,52]. A closer look at Fig.7 indicated that there were valleys around z= 0.42 and 0.47 in M(001)W-1 and M(010)W-1, respectively, corresponding to the location of both the adsorbed water molecules with negative Mulliken charge of -0.03 e. These valleys above surface were able to provide adsorption active sites for new species, such as water molecules.…”
Section: Charge Analysissupporting
confidence: 86%
“…321,412,413 ). Moreover, accounting for dispersion interactions appears to be important to describe the structure and dynamics of liquid water, 414 which otherwise becomes overstructured, 415,416 especially when using GGA functionals.…”
Section: Dispersion Correctionsmentioning
confidence: 99%
“…Especially, surfaces and interlayers of phyllosilicate were studied by DFT calculations [13][14][15]. The quantum chemical calculations can identify the most steady state by comparing the total energies of different structures, and analyzing the interaction between V and oxygen in the lattice, which further affects the related physical and chemical properties of muscovite.…”
Section: Structure and Modelsmentioning
confidence: 99%